The impact of the polish labour immigrants on the labour market in the United Kingdom - Ignac Agnieszka (My University, 2008)
The enlargement of the European Union in 2004 set up new objectives and aims concerning growth and development of economies of each member state. The European states are mostly free-market capitalist systems, which mean that the main role (prices and any intervention) in the marketplace is played by market forces and governmental limitations. Joining Poland to the Union gave labour immigrants a lot of opportunities to find better jobs in other countries of the EU. Some governments chose to take an inevitable action in order to prevent their markets by closing borders for the Polish labour, while others decided to take an advantage from that and provided opportunities for immigrants. The impact of the Polish labour immigrants on the labour market in the UK will be investigated as the aim of this Master Thesis. In order to meet such general aim, I will respond to the following research questions: - What are intended outcomes of the labour mobility within the EU? - What are the factors stimulating labour mobility within EU? - What are the factors stimulating the Polish labour immigration to the UK? - What are demographic and qualification characteristics of the Polish labour immigrants? - What are the influences of the Polish labour immigrants on the British labour market? The dissertation is organized into four chapters, preceded by an introduction and ended by the conclusions. In the first chapter theoretical foundations of labour market will be discussed, namely the meaning of the concept, supply and demand conditions, as well as causes and outcomes of unemployment phenomenon. In the second chapter the basic characteristics of the Polish labour market as well as EU labour market will be analysed, such as supply and demand conditions as well basic demographical structure. The third chapter will present migration phenomenon in the EU. Reasons of international mobility, directions, structure, consequences of labour migrations within the EU countries and finally regulations on the labour mobility within the EU will be discussed. The fourth chapter will cover the analysis of the British labour market before the enlargement of 2004, demographics and qualifications of the Polish immigrant labour and the analysis of impacts of the Polish migrants on the labour market in the UK. The thesis has a theoretical and empirical character. The theoretical part is based on the sources such as: books and text-books, scientific papers and the Internet. In the empirical part, extensive sources of secondary data were utilized, i.e. reports, academic research and data from the statistical offices of Poland (Główny Urząd Statystyczny), the European Union (Eurostat, Eures) and the UK (Home Office, National Institute of Economic and Social Research). The data were processed with the use of descriptive statistics. Moreover, I conducted my own empirical research based on the survey method which resulted in the sample of 100 respondents who were Polish immigrants living and working in the UK. The purpose of the research was to identify reasons for migration and general characteristics of the Polish migrants as employees. The findings contribute and are integrated into to the analysis in chapters 3 and 4.
Wpływ polskiej imigracji zarobkowej na rynek pracy w Wielkiej Brytanii
Keywords: labour immigrants; labour market; United Kingdom; European Union; Poland; demography